Open Fields, Stinking Bodies, and Loud Voices: Britishness and Religious Awakenings in Eighteenth-Century Scotland. Issue 2 (September 2022) - Adkins, Tucker
Abstract : This article interprets the Scottish awakenings through spaces, sounds, and bodies. As southwestern Scots filled late-night, open-air services and repeatedly experienced swooning, screaming, and spectral hauntings, they entered the same 'work' seen throughout the North Atlantic. But the events at Cambuslang and Kilsyth were not commonplace replicas of the outpourings seen elsewhere. The spatial, sonic, and corporeal contexts underlying Scotland's revivals show that the awakeners of northern Britain stridently upended the social expectations indispensable to eighteenth-century 'Britishness'. They specifically did so by seizing and retooling long-held stereotypes regarding Scottish bodies and spaces. In doing so, Scotland's born-again clergy and laypeople joined their co-laborers in thoroughly democratising Protestantism across the British Atlantic.